Gott Hat es schwer mit uns - Tretinjak, Alina (Austria, 2009)
In December 2004, the EU launched a military operation in Bosnia-Herzegovina called Althea. Since then EUFOR troops from 27 European countries have been stationed in Bosnia, their task being to keep in touch with local population and to provide security. But the challenges are many.
Verzio Film Festival Submission
Keywords: Documentary films